(untitled) (Research, Society and Development, 2024)
Brazil is characterized by a rich distribution of flora throughout its territory and excellent biodiversity. In this context, plants, especially those of the Verbenaceae family, have proven to be a valuable source of bioactive compounds with pharmacological potential. This family includes representatives that have shown efficacy against various pathogens, especially those from the genus Lippia L. Its seeds are widely used in folk medicine for their anti-inflammatory, antifungal, antiseptic, antihypertensive, anxiolytic, antileishmanial, antiviral, and digestive properties, among others. This review aims to provide an overview of the therapeutic potential of the Lippia alba species, investigating the parts, components, and biological properties of the plants and highlighting the relevance of this species in the search for natural products for the treatment of various diseases. The studies were selected from 2013 to 2023 through the virtual data platforms Google Scholar, Science Direct, and PubMed, using the search terms: biological activity; ethnopharmacology; Lippia alba; phytochemicals. Through our research, we confirmed that research using the essential oil from the leaves of this species is very popular and has a wide range of pharmacological potential in vitro, in vivo, and in silico. Furthermore, it has been demonstrated that studies on polar and nonpolar extracts of this type are still very rare. Research with other types of samples is envisioned to expand the therapeutic spectrum of the aromatic species.